Astrogliosis: An integral player in the pathogenesis of Alzheimer's disease. (September 2016) - Osborn, Lana M.; Kamphuis, Willem; Wadman, Wytse J.; Hol, Elly M.
Highlights: Astrogliosis is a characteristic feature of Alzheimer's disease (AD). Astrocytes undergo pertinent molecular changes in AD, switching genetic profiles. Functional changes in astrocytes in AD perturb the micromilieu surrounding neurons. Astrocyte dysfunction compromises local and network level neuronal communication. Research focused on astrocytes as therapeutic targets in AD is imperative. Abstract: Alzheimer's disease is the main cause of dementia in the elderly and begins with a subtle decline in episodic memory followed by a more general decline in overall cognitive abilities. Though the exact trigger for this cascade of events remains unknown the presence of the misfolded amyloid-beta protein triggers reactive gliosis, a prominent neuropathological feature in the brains of Alzheimer's patients. The cytoskeletal and morphological changes of astrogliosis are its evident features, while changes in oxidative stress defense, cholesterol metabolism, and gene transcription programs are less manifest. However, these latter molecular changes may underlie a disruption in homeostatic regulation that keeps the brain environment balanced. Astrocytes in Alzheimer's disease show changes in glutamate and GABA signaling and recycling, potassium buffering, and in cholinergic, purinergic, and calcium signaling. Ultimately the dysregulation of homeostasis maintained by astrocytes can have grave consequences for the stability of microcircuits within key brain regions. Specifically, altered inhibition influenced by astrocytes can lead to local circuit imbalance with farther reaching consequences for the functioning of larger neuronal networks. Healthy astrocytes have a role in maintaining and modulating normal neuronal communication, synaptic physiology and energy metabolism, astrogliosis interferes with these functions. This review considers the molecular and functional changes occurring during astrogliosis in Alzheimer's disease, and proposes that astrocytes are key players in the development of dementia.